Built-in self-test implementation on DLX microprocessor - Garcia, Marie Sheridan T.
Chip testing has always been a problem, especially nowadays that integrated circuits tend to become more complex. Testing using external equipment is usually expensive and time consuming. An approach that was used to alleviate this problem was to design the system with a built-in self-test (BIST). Such an approach is cheaper since the need for expensive dedicated testing equipment is minimized. Testing time is also reduced since system testing is done in real time. This project implements BIST architecture on the DLX microprocessor. Existing pipeline registers are transformed into built-in logic block observer (BILBO) registers, a register array with additional operating modes. The registers also function as pattern generator and output analyzer, which are the key components for logic BIST architecture. BILBO helps minimize additional area overhead, and allows thorough diagnosis of structural faults in between the pipeline stages. The implemented DLX microprocessor with BIST achieved a good fault coverage of the system. However, this brought upon notable degradation of the processor's characteristics, particularly on power consumption. The implemented microprocessor is compared with the unmodified DLX microprocessor and is found to have an area overhead of 26.75%, power consumption increase of more than 100%, and decrease in maximum operating frequency by 60%.